Proceedings of the Sixteenth International Cryogenic Engineering Conference/ International Cryogenic Materials Conference : Kitakyushu, Japan, 20-24 May 1996. - Haruyama, Tomiyoshi 1949-; Mitsui, Takeo; Yamafuji, Kaoru 1933-
This book contains the proceedings of the 16th ICEC/ICMC Conference, held in Kitakyushu, Japan, on 20th-24th May 1996. The Proceedings are presented in three volumes containing a total of 476 papers from 1484 authors. The proceedings covers the main areas of: Large Scale Refrigeration. Cryocoolers. Cryogenic Engineering. Space Cryogenics. Application of Superconductivity. Oxide Superconductors. Metallic Superconductors. Metallic Materials. Non Metallic Materials.